Predictive Factors of Gastrointestinal Injuries after Exposure to Sodium Hypochlorite - Ahmad Ghoochani Khorasani; Peyman Erfantalab*; Mahdi Rezai (Iranian Journal of Toxicology, 2017)
Background: Sodium hypochlorite is found in bleaching agents used to cleaning dishes and bleach laundry. The ingestion of sodium hypochlorite causes acute corrosive esophagitis and gastritis. In establishing the diagnosis and therapeutic approach of acute corrosive poisonings, the upper endoscopy has great importance. The aim of this study was to determine predictive factors of gastrointestinal injuries that mandate early endoscopy. Methods: This study consisted of 65 patients presented to Loghman Hakim Toxicology Center, Tehran, Iran with history of sodium hypochlorite bleach exposure from 2010 to 2014. The post-corrosive damage classified according to Kikendal’s grading. Results: There were a total of 19 males and 46 females with a mean age of 34.21 yr old. In upper GI endoscopy, 20% of poisoned patients had abnormal findings. Male gender (P=0.029), presence of hoarseness (P=0.044), nausea and vomiting (P=0.007), sialorrhea (P=0.044) and higher age (P=0.05) were associated with the occurrence of gastrointestinal injuries, but only male gender (OR=5.04), nausea and vomiting (OR=8.97) were independent predictors of gastrointestinal injuries (P=0.03 and P=0.03, respectively). Conclusion: We proposed five factors associated with gastrointestinal injuries, which could be important factors that mandate urgent endoscopy.